Apert Syndrome (Acrocephalosyndactyly): A Rare Syndromic Craniosynostosis - Shrestha, Mahesh; Adhikari, Neelam; Shah, Ganesh (Journal of Nepal Paediatric Society, 2009)
We report a premature infant who had multisutural craniosynostosis with pointed head, syndactyly of 2nd, 3rd and 4th fingers of all four limbs and other findings that were consistent with Apert syndrome. This is perhaps the first case of Apert Syndrome reported from Nepal. Key words: Apert syndrome, craniosynostosis, syndactyly doi: 10.3126/jnps.v29i2.2046 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.92-93